Case Studies on Elderly and Institutionalization in the Southern region of Kerala - Fernandez, Sharon; Zacharias, Lithin; U., Harikrishnan (Journal of Social Work Education and Practice, 2023)
Aging is a period of decline and social attitude towards old age affects the aged population. The practice of institutionalizing the elderly is a broad spreading concept in the modern world, and the old age homes and hospices are growing day by day. The current study aims at exploring the life experiences of the elderly on account of the transition happening due to institutionalization. The current study followed the multiple case study design. The objectives of the study are 1) to understand the social conditions that propel the elderly to choose institutional care, 2) to assess changing the attitude of the elderly towards the society and 3) to determine the coping mechanisms by the elderly in institutions, towards effective adjustment. Samples were selected from the old age homes who were above the age of 65 and institutionalized for at least ten years. Four case studies focused on the current objectives, and semi-structured interview guide was used. The study found that there was some level of psychosocial issues among the elderly and need psychosocial interventions and specialized care for the elderly in the primary, secondary and tertiary levels.